ALLEVIATING DIGITAL ANXIETY IN ONLINE TEACHING: ASSESSING THE ACADEMICS CHALLENGES IN DIGITAL TRANSFORMATION - JAMALUDIN, SITI NOORSIAH; GEDE PRAMUDYA ANANTA, GEDE PRAMUDYA ANANTA; ABD SAMAD HASAN BASARI, ABD SAMAD HASAN BASARI (jatit, 2023)
Although online teaching has experienced an explosive growth rate, digital anxiety is still persistent in many situations; in this context, it has evolved into online teaching anxieties that are yet to be understood. This pilot study aims to investigate the digital anxiety faced among academicians in conducting online teaching. Research is scarce in this area, and studying it helps to understand its significance and impact. A mixed-method approach was used to explore the study. A sample of 65 participants was obtained to conduct the feasibility assessment. The findings showed that academicians are impacted by digital anxiety, which may positively or negatively impact their willingness to accept online teaching. The academicians seem to experience digital anxiety with online teaching due to reasons and factors. It is critical to identify and address sources of anxiety and provide an indication of self-evaluation and assessment of their online teaching experience. Therefore, digital anxiety in online teaching should take centre stage because it represents academicians’ readiness to incorporate various online tools and digital technology into their pedagogical delivery to successfully transform the field of education.